ROOT REINFORCEMENT USING CAST POST CEMENTED WITH DIFFERENT TYPES OF CEMENTS (Mustansiria Dental Journal, 2018)
The purpose of this in-vitro study is to evaluate and compare the fractureresistance of endodontically treated teeth restored using cast posts cemented withdifferent types of cement. Thirty intact human maxillary central incisors were selectedfor this study. The crowns were removed and endodontic therapy were done on theroots, which were then prepared to receive cast posts, after their fabrication, the castposts were cemented with zinc phosphate cement (group I), resin modified glassionomer cement (group II),and resin cement (group III). The samples were subjectedto compressive fracturing loads by a Zwick testing machine at a cross head speed of5mm/min., with an angle of 45º to the long axis of the tooth. The results showed thatthe posts cemented with resin cement exhibited the highest mean failure load followedby posts cemented with resin modified glass ionomer cement , while posts cementedwith zinc phosphate cement exhibited the lowest mean failure load.